2019
DOI: 10.1590/1413-7054201943013219
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters of pigments and agronomic traits in green and purple lettuce

Abstract: Understanding genetics and the gene interactions involved in the expression of certain characteristics becomes a determining factor for better exploration of its use. The development of breeding programs that combine one or more desirable trait into a single cultivar is directly impacted by this lack of knowledge of the genetic bases involved. The objective of the present study was to estimate the genetic parameters involved in pigment expression and agronomic characteristics in lettuce. Parental evaluations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
9
1
1
Order By: Relevance
“…Characters with a high h 2 indicate a high component of the inheritable fraction of the variation (genetic component) in their phenotypic expressions, demonstrating that gains can be achieved through visual selection (Silva et al, 2019), as performed in the present study Peixoto et al (2020) estimated the genetic parameters of eight variables analyzed in 25 lettuce genotypes from the same breeding program (generation F7) and also found high h 2 values for the number of leaves (91.42%), SPAD index (95.96%), and plant diameter (72.77%), confirming the high magnitude of h 2 for these traits. In contrast to this study, Oliveira et al (2019) found low heritability estimates of 6.94% for the chlorophyll index, which may be related to the fact that although it was carried out in the same experimental area with the same cultural practices, different parents were used. Thakur et al (2016) found a heritability value of 58.10% for β-carotene in lettuce, which may have been influenced by the fact that the experiment was conducted under protected conditions.…”
Section: Resultscontrasting
confidence: 94%
See 3 more Smart Citations
“…Characters with a high h 2 indicate a high component of the inheritable fraction of the variation (genetic component) in their phenotypic expressions, demonstrating that gains can be achieved through visual selection (Silva et al, 2019), as performed in the present study Peixoto et al (2020) estimated the genetic parameters of eight variables analyzed in 25 lettuce genotypes from the same breeding program (generation F7) and also found high h 2 values for the number of leaves (91.42%), SPAD index (95.96%), and plant diameter (72.77%), confirming the high magnitude of h 2 for these traits. In contrast to this study, Oliveira et al (2019) found low heritability estimates of 6.94% for the chlorophyll index, which may be related to the fact that although it was carried out in the same experimental area with the same cultural practices, different parents were used. Thakur et al (2016) found a heritability value of 58.10% for β-carotene in lettuce, which may have been influenced by the fact that the experiment was conducted under protected conditions.…”
Section: Resultscontrasting
confidence: 94%
“…Thirteen genotypes were selected by all indices, thus presenting suitable agronomic traits that are promising for advancing generations within the breeding program aimed at obtaining biofortified lettuce strains. SH -Smith (1936) and Hazel (1943); MM -Sum of ranks- Mulamba & Mock (1978); WI -Base-index- Williams (1962) Table 5. Indication of the top 17 lettuce genotypes, selected by the classic indexes proposed by Smith (1936) and Hazel (1943) (SH), Mulamba & Mock (1978) sum of ranks index (MM), and Williams base index (1962) (WI)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A razão CVg/CVe apresentou valores superiores à unidade para as variáveis NF (1,04), ANT (1,21), PEND (1,63) (AZEVEDO et al, 2014;OLIVEIRA et al, 2019;SILVA et al, 2019) e ANT (OLIVEIRA et al, 2019), corroborando os resultados do presente trabalho.…”
unclassified